2020
DOI: 10.1039/c9mo00169g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of aqueous humor after rabbit lensectomy reveals differences in coagulation and immunomodulatory proteins

Abstract: Proteomics of juvenile rabbit aqueous humor was evaluated before and after surgery to determine proteins responsible for postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A total of 27 New Zealand White rabbits (Kuiper Rabbit Ranch, Gary, IN), 6 to 7 weeks of age and weighing between 600 and 900 g, were housed in a 14-hour light/10-hour dark cycle and fed a diet of pelleted chow (Laboratory Rabbit Diet High Fiber 5326; LabDiet, St. Louis, MO) daily and a Timothy hay cube twice per week (Bio-Serv, Flemington, NJ). Based on previous studies with preventative pharmacologic therapies where five or six rabbits per group showed significant postoperative differences clinically and in AH proteins, 14 , 15 eyes of either male or female sex per group were chosen to be randomized to the tPA or control balanced salt solution (BSS) group for postoperative treatments (described below). Rabbits were anesthetized with isoflurane (5% induction, 2.5%–4% maintenance) with 2 L/min of oxygen for surgery and postoperative exams.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 27 New Zealand White rabbits (Kuiper Rabbit Ranch, Gary, IN), 6 to 7 weeks of age and weighing between 600 and 900 g, were housed in a 14-hour light/10-hour dark cycle and fed a diet of pelleted chow (Laboratory Rabbit Diet High Fiber 5326; LabDiet, St. Louis, MO) daily and a Timothy hay cube twice per week (Bio-Serv, Flemington, NJ). Based on previous studies with preventative pharmacologic therapies where five or six rabbits per group showed significant postoperative differences clinically and in AH proteins, 14 , 15 eyes of either male or female sex per group were chosen to be randomized to the tPA or control balanced salt solution (BSS) group for postoperative treatments (described below). Rabbits were anesthetized with isoflurane (5% induction, 2.5%–4% maintenance) with 2 L/min of oxygen for surgery and postoperative exams.…”
Section: Methodsmentioning
confidence: 99%
“…POD3 was chosen because (1) we previously classified this day as the peak of the postoperative response, and (2) it allowed us to compare outcomes with our previous clinical and proteomic studies. 14 , 15 The intraocular pressure (IOP) in each eye was measured using a TonoLab tonometer (Icare USA, Raleigh, NC). Slit-lamp biomicroscopy (SL-D8Z Digital-Ready Zoom Slit Lamp; Topcon Medical Systems, Oakland, NJ) was performed with photographs obtained using a Nikon D810 camera (Nikon USA, Melville, NY) to evaluate each eye in the categories of iris synechiae, pupil dilation in millimeters, and presence or absence of hemorrhage in the anterior chamber.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations